Estrutura espacial e temporal de taxocenoses de anuros de uma área de cerrado, no Centro-Oeste do Brasil - Maragno, Franciéle Pereira (2013)
We investigated the potential factors structuring anuran assemblages using three approaches: i) spatial structure of adult anurans; ii) spatial structure of tadpole assemblages, and iii) temporal structure of reproductive activity. The assemblage of adult anurans was composed by 22 species which co-occurred more frequently than expected by chance at the breeding sites (ponds). Pond area, depth, percentage of flat margin, and pH were the environmental descriptors structuring the assemblage. Additionally, closer ponds were more similar regarding assemblage structure. About 16% of the assemblage structure was explained exclusively by environmental descriptors, 13% exclusively by geographic distance, and 3.7% by the interaction between them. Five species groups were found regarding patterns of pond use, ranging from occasional occurrences to generalists. The tadpole assemblage comprised of 20 species belonging to six ecomorphological guilds, being the benthic the richest guild. We found a positive co-occurrence between species both within that guild and for all species together. Pond area, hydroperiod, and percentage of water covered by vegetation were the main descriptors structuring the assemblages for both scales (species and guilds). Considering species together, 20% of the assemblage structure was explained exclusively by pond environmental descriptors, and spatial influence (3%) was related to those descriptors. For guilds, only environmental descriptors explained the assemblage structure (11%). Groups of similar pond use pattern were segregated by hydroperiod. We detected partitioning among species during the reproductive season, with four guilds regarding temporal pattern: 1. Prolonged calling activity throughout the season; 2. More intense activity at the beginning of the season; 3. More intense at the end, and 4. Occasional occurrences. We found positive correlation of climatic variables with 44% of the species and total abundance of anurans. Our study showed that the assemblages were structured in space and time, with the reproductive activity of the species responding to the local climatic variation. Moreover, we suggest that the maintenance of ponds, which vary in a gradient regarding environmental descriptors, is important to maintain the distinct anuran strategies in this region.